Synthesis of Micro/Nano VO2 Structure by Hydrothermal Method - Nguyen, The Manh; Duong, Hong Quan; Cao, Xuan Thang; Pham, Hung Vuong (Old Journal, 2019)
Vanadium dioxide was synthesized successfully by hydrothermal method. C₂H₅O₄ was played as reducing agent for reducing V⁵⁺ to V⁴⁺ from V₂O₅ precursor. In this article, we have studied the effect of hydrothermal time (6 h–24 h), V₂O₅ concentration (0.1 M–0.4 M) and ratio of V₂O₅/C₂H₅O₄ (1 : 2.4; 1 : 3; 1 : 4) to the structure and morphology of VO₂. Phase formation of VO₂ was analyzed by X-ray diffraction. Morphology and size of micro/nano structures were examined by FE-SEM. The synthesized VO₂ structures were showed variation in particle size and morphology. VO₂ nanorods, micro rotor and nanoplate were observed when ratio of V₂O₅/C₂H₅O₄ was 1 : 2.4, 1 : 3 and 1 : 4, respectively. Moreover, the surface of micro rotor became well-defined morphology with increasing hydrothermal time from 6 h to 24 h. This research showed the way to control the structure and morphology of VO₂ which was useful for VO₂ research area.